Immunotherapies catering to the unmet medical need of cold colorectal cancer - Yuan, Jun; Li, Jiarui; Gao, Ce; Jiang, Chun; Xiang, Ze; Wu, Jian (Frontiers in Immunology, 2022)
As a common malignant tumor of gastrointestinal tract, the incidence of colorectal cancer (CRC) has gradually increased in recent years. In western developed countries, it has even become the second largest malignant tumor next to lung cancer. Immunotherapy is a hot topic in the field of cancer therapy, including immune checkpoint blockade (ICB), adoptive cell therapy (ACT), cancer vaccines and cytokines, aiming to improve the ability of the immune system to recognize, target and eliminate cancer cells. However, cold CRC, which accounts for a high proportion of CRC, is not so reactive to it. The development of immunotherapy to prevent cancer cells from forming "immune escape" pathways to the immune system in cold CRC, has been under increasing study attention. There is proof that an organic combination of radiotherapy, chemotherapy, and several immunotherapies can considerably boost the immune system's capacity to eradicate tumor cells. In this review, we summarized the role of immunotherapy in colorectal cancer. In addition, we propose a breakthrough and strategy to improve the role of immunotherapy in cold CRC based on its characteristics.